2015
DOI: 10.1530/eje-14-0870
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 increases in abdominal subcutaneous fat tissue after supplementation with vitamin D3

Abstract: Objective: The objective was to assess the amount of vitamin D 3 stored in adipose tissue after long-term supplementation with high dose vitamin D 3 . Design: A cross-sectional study on 29 subjects with impaired glucose tolerance who had participated in a randomized controlled trial with vitamin D 3 20 000 IU (500 mg) per week vs placebo for 3-5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 20 publications
5
50
0
1
Order By: Relevance
“…Extraction efficiencies of the [6, 19, 19‐d 3 ]‐vitamin D3 and [6, 19, 19‐d 3 ]‐vitamin D2 were similar and averaged 58 ± 5%. These estimates for recovery and accuracy were comparable to other published results …”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…Extraction efficiencies of the [6, 19, 19‐d 3 ]‐vitamin D3 and [6, 19, 19‐d 3 ]‐vitamin D2 were similar and averaged 58 ± 5%. These estimates for recovery and accuracy were comparable to other published results …”
Section: Methodssupporting
confidence: 88%
“…Prior studies on vitamin D storage in adipose tissue in non‐obese and obese subjects have also focused primarily on subcutaneous fat . Heaney and colleagues investigated the concentration of vitamin D2 and D3 in the subcutaneous tissue of non‐obese but overweight individuals and also found that subjects had greater levels of D3 compared with D2 in their adipose tissue .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although adipose tissue contains substantial amounts of vitamin D [34], very little is known about the storage capacity and how the storage and mobilization processes are regulated. Based on the analysis of vitamin D in fat biopsies from subjects living in northern Norway (latitude 70°) who had participated in an RCT for 3-5 years, Didriksen et al [35] recently estimated that the stores of vitamin D in subcutaneous fat tissue were equivalent to 90 daily doses of 10 lg in the placebo group and 328 daily doses of 20 lg in the group taking vitamin D (oral dose of 500 lg per week). The observations of a clear positive association between vitamin D concentration in fat and serum and a linear increase in circulating 25OHD levels as a function of adiposity volume loss indicate bioavailability of cholecalciferol in fat stores during periods of insufficiency [32,[35][36][37][38].…”
mentioning
confidence: 99%
“…The hormone 1,25(OH) 2 D 3 and its metabolites are lipophilic and are stored in adipose tissue, which might explain the low serum levels of this hormone in obese individuals [10,11]. Didriksen et al [12] demonstrated that after treatment with 1,25(OH) 2 D 3 at 20,000 IU/week for 3-5 years, adipose tissue from obese individuals with impaired glucose tolerance and/ or impaired fasting glucose contains six-fold higher 1,25(OH) 2 D 3 levels than adipose tissue from a placebo group.…”
Section: Introductionmentioning
confidence: 99%